METODE ASII SEBAGAI PEMBINAAN JAMAAH MANIS DI PRM SEROJA CABANG MUHAMMADIYAH MEDAN DENAI - Selamat Pohan; Faizal Lubis (University of Muhammadiyah Sumatera Utara, 2019)
The purpose of this service activity is carried out in order to provide knowledge to sympathizers and residents jamaah shalat jumat masjid taqwa al-huda about the minimum number of branch members Muhammadiyah seroja and also procedures berwudhuk and shalat which have not been sunnah. The form of the activity is through Coaching Jamaah manis (masjid taqwa al-huda neutral, include investigators ) at the Branch Manager Muhammadiyah Seroja by method ASII (Member of Intensive Islamic Studies). Coaching program jamaah manis this will produce a community that understands about Muhammadiyah and can join members persyarikatan ranting seroja PCM Medan Denai. The problem faced by Branch Managers so far is the lack of members when conducting routine recitation. So, in this service the future re-generation will continue the struggle Muhammadiyah, to educate the thinking of Muslim societies, and continue the future muhammadiyah, so that muhammadiyah forward especially in PRM Seroja progress. Keywords: Coaching Jamaah, Member, Muhammadiyah